A comparative study on the adsorption behavior and mechanism of pesticides on agricultural film microplastics and straw degradation products. (September 2022) - Lan, Tao; Cao, Feng; Cao, Licheng; Wang, Ting; Yu, Congcong; Wang, Fenghe
Abstract: Straw will degrade into segment, powder and crystalline cellulose, while the agricultural film will degrade into microplastics (MPs) in farmland soils. The specific surface area of these micro-particles increases and many new functional groups are formed in the degradation process, which can be a good vector of pesticides. To more accurately and truly analyze the risk of main imported substances and their degradation products against pollutants in soil, the adsorption behavior and mechanism of four commonly used pesticides on aged polyethylene microplastics (APE), wheat straw segment (WSS), wheat straw powder (WSP), and straw crystalline cellulose (SCC) were analyzed and compared through batch adsorption experiments and infrared spectrum. The adsorption kinetics of four pesticides on MPs and straw degradation products tended to be pseudo-second-order kinetics; the adsorption isotherms of pesticides on APE and SCC tended to fit the Freundlich model, while on WSP and WSS tended to fit the Langmuir model. The adsorption was a spontaneous endothermic increase process, suggesting that the main adsorption force of pesticides on MPs and straw degradation products was hydrophobic diffusion. The adsorption of pesticides against WSP and WSS still had a certain π-π conjugation and electrostatic interaction. And the adsorption amount on the straw degradation products followed the order of WSP > WSS > APE > SCC, presumably related to the specific surface area and pore volume of the adsorbent. As WSP, WSS could adsorb more pesticides, the straw returning to the field can be used for slow-release of pesticides to reduce the dosage of pesticides. Graphical abstract: Image 1 Highlights: Hydrophobic force mainly contributes to the adsorption. π-π conjugation and electrostatic interaction also play a role in adsorption. The adsorption amount followed the order of WSP > WSS > APE > SCC. The straw returning to the field can be used for slow-release of pesticides.